Interaction second virial coefficients of dimer co-co from new ab initio potential energy surface - Tat, Pham Van (Vietnam Journal of Chemistry, 2014)
The new 5-site ab initio intermolecular interaction potentials of dimer CO-CO were constructed from quantum mechanics using method CCSD(T) with Dunning’s correlation-consistent basis sets aug-cc-pVmZ (m = 2, 3) [7]; ab initio energies were extrapolated to the complete basis set limit aug-cc-pV23Z. The ab initio intermolecular energies were corrected for the basis set superposition error (BSSE) with the counterpoise scheme [8]. The interaction second virial coefficients of dimer CO-CO resulting from the 5-site ab initio analytical potential functions obtained by integration; first-order corrections for quantum effects were included too. The results agree well with experimental data. Keywords: Second virial coefficients, 5-site ab initio potentials.